Individual and Environmental Factors Influencing Recognition of Entrepreneurial Opportunities: Case of Tunisian Companies - Souissi, Mourad; Boujelbene, Younes (Journal of Business and Management Review, 2023)
When entrepreneurs discover an opportunity, they take the risk of exploiting it by seeking out the resources needed to develop a product or service and offer it to customers in the appropriate market. It is therefore essential to understand the factors that influence the recognition of entrepreneurial opportunities. To address this issue, we opted for a quantitative approach, using a sample of 350 entrepreneurs from the city of Sfax. We performed a discriminant analysis to test our hypotheses and determine the contribution of each factor to the process of identifying business opportunities. This article presents a literature review and the results of the studies examined concerning the key factors influencing the recognition of business opportunities. The results of our research can help young entrepreneurs understand the critical factors that will prompt them to quickly and effectively identify entrepreneurial opportunities with a view to exploiting them in business creation. Additionally, the information provided in this article could serve as a guiding resource for researchers interested in delving deeper into the determinants of entrepreneurial opportunity recognition.